2017
DOI: 10.1080/09669582.2017.1359277
|View full text |Cite
|
Sign up to set email alerts
|

World Heritage as a placebo brand: a comparative analysis of three sites and marketing implications

Abstract: World Heritage as a placebo brand: A comparative analysis of three sites and marketing implicationsThe UNESCO World Heritage List is often regarded as a successful tourism brand that motivates site nominations. However, there is relatively little research dealing specifically with World Heritage (WH) brand attraction effects, and what does exist shows conflicting results. There is a significant research gap in terms of awareness of the WH brand and its potential impact on visitation, which this study seeks to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 58 publications
1
28
0
4
Order By: Relevance
“…In addition, with this model, museums have the capacity to attract potential visitors, taking into account the different factors analyzed. It is possible to confirm the affirmation of the existence of levels of consciousness in groups of visitors to cultural heritage (Adie et al, 2018), in this case in museums.…”
Section: Implications For the Management Of The Museummentioning
confidence: 71%
“…In addition, with this model, museums have the capacity to attract potential visitors, taking into account the different factors analyzed. It is possible to confirm the affirmation of the existence of levels of consciousness in groups of visitors to cultural heritage (Adie et al, 2018), in this case in museums.…”
Section: Implications For the Management Of The Museummentioning
confidence: 71%
“…As regards gender variable, there is a dispute; since, while some research concludes that women have greater preference for heritage tourism [3,18,20,23], other empirical studies conclude otherwise [14,19,39,43]. However, these researches indicate that there are no significant gender differences.…”
Section: Sociodemographic Profile Of Touristsmentioning
confidence: 99%
“…However, taking gender as a reference to identify differences in relation to motivations, the experiences or satisfaction of tourists visiting a Heritage of Humanity site are a source of dispute. For example, research such as that of Adie et al [70], Chen and Huang [56], and Correia et al [30] identified no gender differences, while the research of Ramires et al [38], Wang [24], and Huete-Alcocer et al [71] did, noting that women are more willing to visit heritage destinations. However, this research, according to Pereira and Silva [21], is not focused on exploring gender differences, but more on how women perceive their travel, how they construct their experiences, and how satisfied they are in their visit to a place-in this case, a heritage site.…”
Section: Sociodemographic Profile Of Touristsmentioning
confidence: 99%